Psychophysiological effects of stress in diabetic patients, ischaemic heart patients and healthy subjects - Bradley, Clare (1978)
This thesis is concerned with the relationships between physiological changes and subjective and behavioural responses to stress. The effects of noise stress were examined under laboratory conditions, and retrospective studies of stress induced by life events were also carried out.